2022
DOI: 10.1038/s41586-022-04508-4
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab plus chemotherapy or ipilimumab in gastro-oesophageal cancer

Abstract: Standard first-line chemotherapy results in disease progression and death within one year in most patients with human epidermal growth factor receptor 2 (HER2)-negative gastro-oesophageal adenocarcinoma1–4. Nivolumab plus chemotherapy demonstrated superior overall survival versus chemotherapy at 12-month follow-up in gastric, gastro-oesophageal junction or oesophageal adenocarcinoma in the randomized, global CheckMate 649 phase 3 trial5 (programmed death ligand-1 (PD-L1) combined positive score ≥5 and all rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
211
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(217 citation statements)
references
References 32 publications
5
211
0
1
Order By: Relevance
“…We retrieved 6680 potentially relevant trials from PubMed, Embase and the Cochrane Library databases. After removing duplicates and screening titles, abstracts, and full texts, 50 articles met our inclusion criteria and were included in the meta-analysis ( 21 70 ). There was a high-risk bias in 11 clinical trials, mainly due to incomplete reported data and other biases in 5 studies.…”
Section: Resultsmentioning
confidence: 99%
“…We retrieved 6680 potentially relevant trials from PubMed, Embase and the Cochrane Library databases. After removing duplicates and screening titles, abstracts, and full texts, 50 articles met our inclusion criteria and were included in the meta-analysis ( 21 70 ). There was a high-risk bias in 11 clinical trials, mainly due to incomplete reported data and other biases in 5 studies.…”
Section: Resultsmentioning
confidence: 99%
“…For tumors of the esophagus (both squamous cell carcinoma and adenocarcinoma), esophago–gastric junction and stomach, recent studies clarified the pivotal role of the 22C3 (Dako) and 28-8 (Dako) clones [ 35 , 36 , 37 ]. At the immunohistochemical level, the staining pattern should be assessed using the CPS.…”
Section: Introductionmentioning
confidence: 99%
“…At the immunohistochemical level, the staining pattern should be assessed using the CPS. The CPS thresholds for considering a specific case as “positive” (i.e., eligible for immunotherapy) in this context represent a changing landscape, with current evidence suggesting a threshold of five for gastric tumors, also including those of the esophago–gastric junction, and of 10 for esophageal malignancies [ 35 , 36 , 37 ]. Given that this scenario is in constant and rapid evolution, the general suggestion for pathologists assessing PD-L1 in esophageal–gastric specimens is to provide the exact CPS score in the pathology report.…”
Section: Introductionmentioning
confidence: 99%
“…The CheckMate 649 trial evaluated PD-1 inhibitor-based first-line chemotherapy [ 34 , 41 ]. Participants with unresectable tumors, PD-L1 CPS ≥ 5, non-HER2-positive GC, GEJ, or esophageal adenocarcinoma were classified into 3 groups and received nivolumab plus chemotherapy (oxaliplatin plus capecitabine or fluorouracil, leucovorin), nivolumab plus ipilimumab, or chemotherapy alone, respectively.…”
Section: Immune Checkpoint Inhibitors For Gastric Cancermentioning
confidence: 99%